Answer:
x = 1
Explanation:
to evaluate for the value of x we would in the expression
5x-4+2x=3
we will collect the like terms
5x + 2x - 4 = 3
7x - 4 = 3
7x = 3 +4
7x = 7
divide both sides by the coefficient of x which is 7
7x/7 = 7/7
x = 1
to check if your answer is correct you will put the value of x = -1 into the expression 5x - 4 + 2x = 3 and see if the left handside is equal to the right handside.
5(1) - 4 + 2(1) = 3
5 - 4 + 2 = 3
1 + 2 = 3 ............................................................................................................................. proved